2022
DOI: 10.1016/j.paid.2022.111531
|View full text |Cite
|
Sign up to set email alerts
|

Big Five traits predict stress and loneliness during the COVID-19 pandemic: Evidence for the role of neuroticism

Abstract: The rapid outbreak of the coronavirus disease (COVID-19) has affected citizens' daily lives in an unprecedented way. To curb the spread of the pandemic, governments have taken numerous measures such as social distancing and quarantine, which may be associated with psychological consequences, namely stress and loneliness globally. To understand differential associations of personality traits with psychological consequences of COVID-19, we utilize data from a sample of 99,217 individuals from 41 countries collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 61 publications
7
22
1
Order By: Relevance
“…Consistent with our results, a large COVID-19 survey of nearly 100,000 people in the general population also showed that neuroticism is significantly associated with loneliness in times of crises. ( Ikizer et al, 2022 ) In a prior study in MS, neuroticism was associated with depression and cognitive impairment. ( Kever et al, 2022 ) Based on the standardized coefficient in the stepwise regression models, greater social support can offset some of the feelings of loneliness associated with the neuroticism trait.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with our results, a large COVID-19 survey of nearly 100,000 people in the general population also showed that neuroticism is significantly associated with loneliness in times of crises. ( Ikizer et al, 2022 ) In a prior study in MS, neuroticism was associated with depression and cognitive impairment. ( Kever et al, 2022 ) Based on the standardized coefficient in the stepwise regression models, greater social support can offset some of the feelings of loneliness associated with the neuroticism trait.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, it is crucial to understand the approach of neurotic nurses to their work during the pandemic. Though studies explain the effect of neuroticism on individual outcomes, such as stress, loneliness, and boredom during the pandemic ( Caci et al, 2020 ; Ikizer et al, 2022 ), we focused on organizational outcomes such as work engagement. Nurses’ work engagement has societal implications and was critical during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggest a minimum of 200 participants per group (Kline, 2005), while others advise a minimum of 93 participants (van de Vijver et al, 2019). Based on indications in the literature and our own experience in cross-cultural data analysis (Ikizer et al, 2022;Kowal et al, 2020b;Kowal et al., 2021, we decided to test the equivalence of invariance on a minimum number of 100 participants per linguistic group.…”
Section: Power Analysismentioning
confidence: 99%